ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI KONSUMEN PADA MINIMARKET DI KECAMATAN BANJARSARI KOTA SURAKART - Budiningtyas, Fitria Sari (2011)
The purpose of in this research is to analyze factors influencing consumer in choosing Mini Market as place of going shopping consumer market in district of Banjarsari Surakarta the year 2011. Population which will be checked is all public in Kecamatan Banjasari Surakarta which is consumer market in area Kecamatan Banjarsari Surakarta, while sample applied 100 publics. Data analytical method applied in this research is factor analysis, multiple regression, test t, F test, and determination test. Before done data analysis beforehand is done examination of classic assumption. The conclusion obtained is (1) factors analysis test result it is concluded that there are 15 variables having influence to consumer in choosing market in sub-district Banjarsari Surakarta (2) there is 6 new factor influencing consumer in choosing market that is quality of service (F1), various and quality of product (F2), location and promo (F3), perception about price ( F4), design market (F5), and attribute physical of shop (F6), (3) there is influence quality of service (F1), various and quality of product (F2), location and promo (F3), perception about price (F4), design market (F5), and attribute physical of shop (F6) to election of consumer in choosing mini of market in sub-district Banjarsari Surakarta, and ( 4) service quality factor is factor that is most dominant to election of consumer in choosing mini of market in sub-district Banjarsari Surakarta.